n = 1 ∑ 1 2 n 2 + n = 2 ∑ 1 2 n 2 + n = 3 ∑ 1 2 n 2 + ⋯ + n = 1 1 ∑ 1 2 n 2 + n = 1 2 ∑ 1 2 n 2 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
GJ, same way
Did the same way. Cant comment on your formatting since I never write solutions
Small correction in the solution. In the explanation, it should be 1 2 2 and 1 1 2 , not 1 2 1 2 and 1 1 1 1 .
The series can be written as ∑ i = 1 1 2 n 2 - ∑ i = 1 1 2 n 2 ( 12 - n) = ∑ i = 1 1 2 n 3 = 6084
Problem Loading...
Note Loading...
Set Loading...
No need to do all that stuff.
If we expand the series, we can see that 1 2 2 appears exactly 12 times (as a sum), 1 1 2 appears 11 times and it keeps going in this way.
So we can write: 1 2 ⋅ 1 + 2 2 ⋅ 2 + . . . + 1 1 2 ⋅ 1 1 + 1 2 2 ⋅ 1 2 Or in the seguent way (easier and plain): 1 3 + 2 3 + . . . + 1 1 3 + 1 2 3 That is the sum of the first 12 cubes
Now use the generalized formula to calculate the sum of the first n cubes and put n = 1 2 k = 1 ∑ n k 3 = 4 n 2 ⋅ ( n + 1 ) 2 = 4 1 2 2 ⋅ ( 1 3 ) 2 = 6 0 8 4